Simultaneous detection of force and tunneling current in electrolyte solution by using qPlus sensor - Kobayashi, Naritaka; Hojo, Masayuki; Baba, Kengo; Sakuta, Ken (Review of scientific instruments, 2023)
We have developed a sensor for simultaneous measurement of atomic force microscopy (AFM) and scanning tunneling microscopy (STM) under liquid environments. The sensor, which is based on the qPlus sensor, is equipped with an insulated conductive tip. Owing to its electrical insulation except for the tip apex, the developed sensor enabled simultaneous detection of tip–sample interaction force and tunneling current, suppressing the Faradaic leakage current. As a fundamental demonstration, we performed simultaneous AFM/STM imaging in an electrolyte solution by using the developed sensor.